2014
DOI: 10.1113/jphysiol.2013.267351
|View full text |Cite
|
Sign up to set email alerts
|

Reduced contribution of endothelin to the regulation of systemic and pulmonary vascular tone in severe familial hypercholesterolaemia

Abstract: Key pointsr Familial hypercholesterolaemia (FH) causes vascular dysfunction involving reduced nitric oxide (NO) bioavailability and limits exercise-induced vasodilatation in the systemic, but not pulmonary, vasculature.r The mechanism(s) underlying blunted exercise-induced systemic vasodilatation in FH are unclear but may involve enhanced endothelin-1 (ET-1)-mediated vasoconstriction resulting from lessened NO-dependent inhibition.r In a chronically instrumented swine model of FH, ET-1 receptor inhibition in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…In spite of the extensive research, the cardioprotective effect of exercise which is mediated by redox changes is still a question of debate. Several studies showed that hyperlipidemia impairs exercise capacity itself [ 273 ] or the effect of physical activity [ 272 , 274 , 275 ]. However, a number of exercise programs have effectively reversed hypercholesterolemia-induced changes mainly within the vasculature by improving NO bioavailability in both animal studies and humans [ 276 281 ].…”
Section: Modulation Of Hypercholesterolemia-induced Oxidative/nitrmentioning
confidence: 99%
“…In spite of the extensive research, the cardioprotective effect of exercise which is mediated by redox changes is still a question of debate. Several studies showed that hyperlipidemia impairs exercise capacity itself [ 273 ] or the effect of physical activity [ 272 , 274 , 275 ]. However, a number of exercise programs have effectively reversed hypercholesterolemia-induced changes mainly within the vasculature by improving NO bioavailability in both animal studies and humans [ 276 281 ].…”
Section: Modulation Of Hypercholesterolemia-induced Oxidative/nitrmentioning
confidence: 99%
“…; Bender et al. , ). We have found that this protocol yields greater consistency in the development of coronary atherosclerosis than with the standard pig chow.…”
Section: Methodsmentioning
confidence: 98%
“…Endothelin (ET), first described by Yanagisawa in 1988 [ 1 ], is a 21-amino acid peptide with strong vasoconstrictor and mitogenic activities [ 2 , 3 , 4 , 5 ]. ET-1 is the most abundant endothelin and plays an important role in the cardiovascular system and cardiovascular diseases, such as regulating vascular tone, cardiac contractility, water hemostasis and the production of rennin and aldosterone [ 6 , 7 ]. The biological effects of ET-1 are mediated by two G protein-coupled receptors, ETA receptor (ETAR) and ETB receptor (ETBR) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%